2018
DOI: 10.4103/jomfp.jomfp_69_17
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma metastatic to the maxillary gingiva: A case report and review of the literature

Abstract: Tumor metastasis to the oral cavity is rare and is usually an indication of late-stage disease and poor prognosis. While, there are reports of renal cell carcinoma (RCC) metastatic to oral cavity, vast majority of them are to the jaw. Herein, we present a case of a 78-year-old woman with RCC metastasis limited to the oral soft tissue without any bone involvement. As the lesion solely involved maxillary gingiva, it clinically mimicked that of a pyogenic granuloma, which is a reactive, nonneoplastic condition. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Our research strategy revealed a total of 226 relevant articles. 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 The results of the current research were expressed in descriptive statistics. A total of 250 patients were included with 168 males and 67 females with a male to female ratio of 2.5:1.…”
Section: Resultsmentioning
confidence: 99%
“…Our research strategy revealed a total of 226 relevant articles. 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 The results of the current research were expressed in descriptive statistics. A total of 250 patients were included with 168 males and 67 females with a male to female ratio of 2.5:1.…”
Section: Resultsmentioning
confidence: 99%
“…Oral metastases are much less common and less familiar to physicians. Of all malignant tumours in the oral cavity, approximately 1% are metastatic lesions 1 …”
Section: Discussionmentioning
confidence: 99%
“…In men, primary cancer of the kidney is the second most common source of soft tissue oral metastasis, responsible for 14% of cases in a series reported by Hirschberg 5 . A recent review of RCC metastasising to the soft tissue of the oral cavity found 25 reported cases between 2007 – 2017 1 . In most of these cases there were other metastases either known at diagnosis or discovered shortly thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations